Desenvolvimento de imobilizado bactéria-biocarvão para aplicações agrícolas e ambientais - Schommer, Vera Analise (2025)
The immobilization of bacteria in biochar is a promising technique for use in agricultural and environmental applications. This approach is reported as a way to reduce environmental stress on inoculated microorganisms in degraded and contaminated environments, providing greater stability and microbial survival, which can improve environmental quality. The literature specifies three main techniques for immobilizing bacteria in biochar: (1) growth in biochar; (2) adsorption after microbial growth; and (3) pre-activation before immobilization. The mechanism of this process is divided into two stages: (i) adsorption of microbial cells on the biochar surface; and (ii) biofilm formation. In reports on agricultural and environmental applications, biochar can act as a soil conditioner, a contaminant adsorbent, and provide a protective habitat for microorganisms, while microorganisms contribute to nutrient availability and the release of secondary metabolites that promote plant growth, as well as the decontamination or reduction of contaminant bioavailability. Given this context, the objective was to develop a biochar-based material with immobilized bacteria for agricultural and environmental applications. First, two grape residue biomasses (raw and composted) and two pyrolysis temperatures (350°C and 650°C) were tested to produce biochar in an industrial reactor. The immobilization process was carried out through bacterial cultivation in the presence of biochar. The bacteria Bacillus subtilis BEIB-18 and Priestia megaterium BEIB-30 immobilized in biochar were applied via seed treatment to verify their effects on wheat seedlings. Secondly, in search of improvements, different biochars were produced in a bench-scale reactor using factorial design (25-1), varying the precursor (raw and composted biomass), CO2 activation (for 0 and 60 minutes), heating rate (5 and 15 °C.min⁻¹), temperature (500 and 800 °C), and pyrolysis time (30 and 90 minutes) to investigate the influence of these variables on the physical and chemical properties of the biochars. The best biochars were then evaluated for their bacterial cell immobilization capacity. Bacillus subtilis BEIB-18 immobilized in optimized biochar was applied in the bioremediation of Cr(VI) in an aqueous medium. This resulted, first, in bacteria-biochar immobilization with a satisfactory concentration of immobilized microorganisms (8.96 log CFU.g⁻¹ for Bacillus subtilis and 8.01 log CFU.g⁻¹ for Priestia megaterium), maintaining cell viability for at least 8 months at room temperature. In the seedling test, treatments with biochar and bacteria-biochar immobilization showed statistically significant positive differences compared to the control, highlighting its potential in promoting root development in wheat cultivation. Secondly, the optimization of biochar production indicated that the composted grape residue precursor, pyrolysis at 800°C, CO2 activation, and a residence time of 30 minutes were the most favorable conditions for producing the immobilization material (9.41 log CFU.g⁻¹ of Bacillus subtilis). In the bioremediation of Cr(VI) in an aqueous medium, the results were also promising, with 48.44% removal and Cr(VI) reduction (109 mg.g⁻¹), indicating a combined effect between the bacteria and biochar in removing and reducing the toxicity of the toxic metal. In both tests, studies on the properties of biochar indicated that a mesoporous, alkaline material (pH 9) with the presence of nutrients and oxygen-containing functional groups is favorable for microbial immobilization. In this context, this work aims to contribute to the state of the art in increasing agricultural sustainability and improving bioremediation techniques, thereby contributing to the achievement of some Sustainable Development Goals (SDGs): SDG 2 (Zero Hunger and Sustainable Agriculture), SDG 6 (Clean Water and Sanitation), SDG 9 (Industry, Innovation, and Infrastructure), SDG 14 (Life Below Water), and SDG 15 (Life on Land).